Test–retest Reliability in Reporting the Pain Induced by a Pain Provocation Test: Further Validation of a Novel Approach for Pain Drawing Acquisition and Analysis. Issue 2 (15th March 2016) - Leoni, Diego; Falla, Deborah; Heitz, Carolin; Capra, Gianpiero; Clijsen, Ron; Egloff, Michele; Cescon, Corrado; Baeyens, Jean‐Pierre; Barbero, Marco
Abstract: Background: Pain drawings (PD) are frequently used in research to illustrate the pain response to pain provocation tests. However, there is a lack of data on the reliability in defining the extent and location of pain. We investigated the test–retest reliability in reporting an acute painful sensation induced by a pain provocation test using a novel approach for PD acquisition and analysis in healthy volunteers. Methods: Forty healthy volunteers participated. Each participant underwent 2 upper limb neurodynamic tests 1 (ULNT1), once to the point of pain onset (PO) and once until the point of submaximal pain (SP). After each ULNT1, participants completed 2 consecutive PD with an interval of 1 minute. Custom software was used to quantify the pain extent and analyze the pain overlap. The test–retest reliability of pain extent was examined using Intraclass Correlation Coefficient (ICC2, 1 ) and Bland–Altman plots. Pain location reliability was examined using the Jaccard similarity coefficient (JSC). Results: The ICC values for PO and SP were 0.98 (95% CI: 0.96–0.99) and 0.97 (95% CI: 0.95–0.98), respectively. The mean difference and 95% limits of agreement (± 1.96 SD) in the Bland–Altman plots were 14 pixels (−1080;1110) for PO, and 145 (−1610;1900) for SP. The median JSCs (Q1;Q3) were 0.73 (0.64;0.80) for PO and 0.76 (0.65;0.79) for SP. Conclusions: Pain drawings is a reliable instrument to investigate pain extent and pain location in healthy individuals experiencing an acute painful sensation induced by a pain provocation test.